Letter from an Unknown Woman and the Melancholia of Philosophy: Cavell, Austin, Derrida - Jukić, Tatjana (2009)
My text analyzes the agency of melancholia and melodrama in the philosophy of Stanley Cavell, where they labor as a sinthome of what in philosophy is memory. This analysis hinges on a close reading of Stefan Zweig's Letter from an Unknown Woman as a point of access to articulating these concerns, as Cavell's own writing on the subject (in Contesting Tears) hinges on a close reading of Max Ophüls's film based on Zweig's novella, but only after Cavell has explicitly excluded Zweig from his argument. Moving from this exclusion to Cavell's philosophizing of birthplace via Austin and Derrida (in Philosophical Passages), I propose a deconstruction of that position in inheriting and remembering philosophy today, even where it invokes the problem of technics, which still depends on an identitarian politics.
Projekt MZOS
Projekt MZOS
ENG